Some possible legal approaches about ‘efficacy’ as research category of alternative methods for conflict solution (AMCS) - Lezcano Miranda, Martha Eugenia; Vásquez-Santamaría, Jorge Eduardo (Temas Socio-Jurídicos, 2018)
By questioning the applicability of Alternative Methods for Conﬂict Solution (AMCS) in public contracts of working, consulting and concession in the Metropolitan Area of Valle de Aburrá in the light of Law 80 of 1993, it was showed the absence of previous methodological construction on efcacy as analytical category of juridical setting and sociojuridical objects. So it is valid to ask which juridical approaches allow the category ‘efcacy’ to intermediate the object of some juridical research? This work is centered in showing some possible implications of efcacy as category for juridicalresearch, by a theoretical foundation of its methodological development, from contributions of Law General Theory and statements about efcacy as general principle in the practice of administrative function and public deals. From two proposed dimensions, in the conclusions is stated that efcacy is a category that allows a particular research approach, resulting both in a defnite searching criterion and in the validation of juridical and sociojuridical objects, such as conﬂict resolution in public contracts. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">